“Teorema” e San Paolo. Citazioni pasoliniane fra cinema e letteratura - Alessandra Grandelis (Parole Rubate, 2012)
Comparing Pasolini’s use of cinema and literature, this article examines the references and quotations that appear in Teorema, and dwells upon the two versions of it (novel and film), and the various allusions used each time (literary, pictorial, and biblical). With regard to the scriptural references, the attention will then be shifted to Abbozzo di una sceneggiatura per un film su San Paolo, a film project never carried out that makes a very different use of allusions and quotations than Teorema.